Cellular scars and local crosstalk in relapsing psoriasis: an example of a skin sticking disease. (19th September 2020) - Gallais Sérézal, Irène; Cheuk, Stanley; Martini, Elisa; Eidsmo, Liv
Abstract: Psoriasis is an inflammatory disease that arises in genetically predisposed individuals. Chronic skin lesions that contain activated immune cells can persist for years. Systemic inhibition of TNF, IL‐17 and IL‐23 cytokines has revolutionized psoriasis care during the recent decades. Unfortunately, local relapse of disease is common at previously inflamed sites after cessation of treatment. This highlights that fundamental pathologic alterations of the affected tissues are not completely resolved during clinical remission. Here, we present arguments for a local disease memory located in both dermis and epidermis in psoriasis skin. We decipher different cellular components and intercellular crosstalk that sustain local disease memory and amplify disease relapse in human psoriasis. Decrypting the mechanisms underlying the establishment and persistence of pathogenic memory cells in resolved psoriasis may provide new therapeutic perspectives aimed at long‐term remission of psoriasis.